PERGESERAN NILAI: TINJAUAN PSIKOLOGIS SEBAGAI AKIBAT PENERAPAN TEKNOLOGI INTERNET DALAM PEMBELAJARAN - Nila Dameria; Happy Fitria (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Shifting values in terms of the psychological side is an important review in the current situation. The development of technology, especially the internet, has many impacts on learning, especially on the individual side of students. The purpose of this research is to see what shifts in values or characters are implicated from the application of the internet in the learning process. The method used in this study is the quality method, with secondary data sources that are processed from literature. The results of this study are there is a shift in value when viewed from the psychological aspects due to the application of internet technology in learning. In the psychological review of education which becomes the main scope are contextual teaching and learning, process of teaching and learning, outcomes of teaching and learning. Educational psychology focuses on the situation and conditions of learning, the learning process and the results achieved from the learning process through the learning situations created. The condition of learning by applying internet technology provides space for students to obtain extensive information about whatever they want to know. With ease, students get any information that makes the desire to be serious in learning is not so optimal. In the psychological side of the value it means that it is being eroded by the application of a new technology.